Multicenter clinical experience with non‐invasive cell‐free DNA screening for monosomy X and related X‐chromosome variants. (9th February 2023) - Bedei, Ivonne; Gehrke, Tascha; Gloning, Karl‐Philipp; Meyer‐Wittkopf, Matthias; Willner, Daria; Krapp, Martin; Scharf, Alexander; Degenhardt, Jan; Heling, Kai‐Sven; Kozlowski, Peter; Trautmann, Kathrin; Jahns, Kai M.; et al.
Abstract: Objective: We aimed to investigate how the presence of fetal anomalies and different X chromosome variants influences Cell‐free DNA (cfDNA) screening results for monosomy X. Methods: From a multicenter retrospective survey on 673 pregnancies with prenatally suspected or confirmed Turner syndrome, we analyzed the subgroup for which prenatal cfDNA screening and karyotype results were available. A cfDNA screening result was defined as true positive (TP) when confirmatory testing showed 45, X or an X‐chromosome variant. Results: We had cfDNA results, karyotype, and phenotype data for 55 pregnancies. cfDNA results were high risk for monosomy X in 48/55, of which 23 were TP and 25 were false positive (FP). 32/48 high‐risk cfDNA cases did not show fetal anomalies. Of these, 7 were TP. All were X‐chromosome variants. All 16 fetuses with high‐risk cfDNA result and ultrasound anomalies were TP. Of fetuses with abnormalities, those with 45, X more often had fetal hydrops/cystic hygroma, whereas those with "variant" karyotypes had different anomalies. Conclusion: Both, 45, X or X‐chromosome variants can be detected after a high‐risk cfDNA result for monosomy X. When there are fetal anomalies, the result is more likely a TP. In the absence of fetal anomalies, it is most often an FP or X‐chromosome variant. Key points: What is already known about this topic? Cell‐free DNA (cfDNA) screening can detect monosomy X and other X chromosome variants associated with a Turner syndrome phenotype, but performance is poorer than for trisomy 21. Little is known about the performance of cfDNA screening for X chromosome abnormalities in the presence of fetal structural anomalies. What does this study add? A positive cfDNA screening result for monosomy X is more often confirmed when fetal anomalies are detected. In the absence of fetal anomalies, a positive cfDNA screening result is more often a false positive or associated with mosaicism or other X‐chromosome variants.